In vitro activity and beta-lactamase stability of two oral cephalosporins, ceftetrame (Ro 19-5247) and cefetamet (Ro 15-8074). - Neu, H C (1986)
Ceftetrame (Ro 19-5247) and cefetamet (Ro 15-8074), two new orally administered aminothiazolyl imimomethoxy cephalosporins, inhibited hemolytic streptococci and Streptococcus pneumoniae at less than or equal to 0.5 micrograms/ml but were less active against staphylococci than were cephalexin and cefaclor. They did not inhibit S. faecalis, S. faecium, Listeria monocytogenes, Corynebacterium JK species, or Pseudomonas aeruginosa. Haemophilus influenzae, Branhamella catarrhalis, and Neisseria gonorrhoeae, including ampicillin-resistant isolates, were inhibited at less than 0.25 micrograms/ml. Both agents inhibited Escherichia coli, Klebsiella pneumoniae, K. oxytoca, Proteus mirabilis, Salmonella species, Shigella species, Citrobacter diversus, and Aeromonas hydrophila resistant to ampicillin, cephalexin, and cefaclor at less than or equal to 2 micrograms/ml, although many isolates of Enterobacter cloacae, Citrobacter freundii, and Serratia marcescens resistant to cefotaxime were not inhibited by these agents. A marked inoculum effect was noted for Enterobacteriaceae carrying the Richmond-Sykes type 1A chromosomally mediated beta-lactamases, but plasmid-mediated beta-lactamases did not hydrolyze the compounds. Both drugs inhibited the chromosomally mediated beta-lactamase of E. cloacae, P99.